Enteral Nutrition Target of Critical Patients in The Intensive Care Unit - Aktaş, Hasan; Bozbay, Süha; Kayhan, Oğuzhan; Demirkıran, Oktay (Cerrahpaşa Medical Journal, 2019)
Objective: Nutritional support (NS) is an important part of the treatment of patients in the intensive care unit (ICU). The preferred method for NS is enteral nutrition (EN). The aim of the present study was to investigate the time of initiation of NS for patients admitted in the ICU, whether the nutritional target dose was achieved and if not, the factors that led to this. Methods: The study was planned retrospectively and included patients aged between 18 and 90 years, followed up between 01/01/2017 and 12/31/2018 in the emergency ICU. Patients’ demographic characteristics, the time of nutritional supplementation initiation, the time of achieving the target, and EN termination reasons during the nutritional status were evaluated. Results: A total of 152 patients were analyzed. Of the 152 patients, 49 were investigated for enteral feeding. Enteral NS was provided via nasogastric tube (93%) and percutaneous endoscopic gastrostomy (PEG) (7%). The mean time to start EN was 10.3 (±8.6) h. The mean time to reach the target was 14.1 (±5.9) h in 96% of the patients. In 2 patients, the target dose could not be reached due to vomiting and excess gastric residual volume. Thirty (61%) patients had problems during NS and EN interrupted. Conclusion: Any critically ill patient who has been in intensive care for >48 h should be considered at risk for malnutrition. In patients undergoing intensive care, it is recommended to start enteral feeding within 48 h (early enteral feeding) if there is no oral intake. Cite this article as: Aktaş H, Bozbay S, Kayhan O, Demirkıran O. Enteral Nutrition Target of Critical Patients in The Intensive Care Unit. Cerrahpasa Med J 2019; 43(3): 92-96.